Experimental Investigation of Vibration Characteristics in a Centrifugal Pump with Vaned Diffuser. (24th December 2018) - Wang, Kai; Lu, Xin; He, Xianghui
Abstract : In order to investigate the vibration characteristics of centrifugal pump, a centrifugal pump with vaned diffuser whose specific speed is 190 was chosen for this research. Both the experiments of energy performance and vibration characteristics of the pump were performed. The results indicate that when flow rate of the pump is 270 m 3 /h, the head is 15.03 m and the efficiency is 71.47%. The maximum efficiency is 71.71% when the flow rate of the pump is 233 m 3 /h and the head is 16.92 m. And a wide frequency band of vibration appears at 600 Hz at outlet flange of the pump. The vibration intensity at the outlet flange is largest. The vibration intensities at both sides of bearing casing are slighter than those at outlet flange and larger than those at motor base. The vibration intensity at the motor base is larger than that at pump base, and the vibration intensity at the pump body is the lowest. The vibration intensity of monitoring point M4 in the X direction under 0.8 Q d is 1.27 mm/s, which is the maximum under three flow rates.